Pendampingan Budidaya Padi Organik Intensif dan Presisi Berbasis Iot pada Kelompok Tani Tunas Baru Kecamatan Rantau Panjang Kabupaten Ogan Ilir: Intensive and Precise Organic Rice Cultivation Assistance Based on IoT for the Tunas Baru Farmer Group, Rantau Panjang District, Ogan Ilir Regency - Fadli, Rahmad; Suwandi, Suwandi; Irsan, Chandra; Pratama, Rahmat (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Community Service in IoT-Based Organik Rice Farming Assistance, conducted through demonstration plots. The goal is to address productivity issues in rice farming on floodplain swamp lands. This issue can be addressed by applying a sustainable farming approach that combines technology with organic materials. The activities held with the Tunas Baru farmer group in Kotadaro Village have shown positive results. The group’s 27.5-hectare land, which had low productivity in the second season, has shown improvement due to increased soil fertility and a significant reduction in pest and disease attacks below harmful economic thresholds. The technology used in this program includes pH monitoring sensors, and NPK content sensors, among others. Additionally, the program teaches the production of soil conditioners such as biocompost, liquid Beauveria, and liquid Trichoderma. Over 83% of the farmer group members involved in the program understand the long-term benefits and the potential for increased productivity due to the adoption of sustainable farming practices with a technological approach.